If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3n = 7n + 1 Reorder the terms: 5 + -3n = 1 + 7n Solving 5 + -3n = 1 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. 5 + -3n + -7n = 1 + 7n + -7n Combine like terms: -3n + -7n = -10n 5 + -10n = 1 + 7n + -7n Combine like terms: 7n + -7n = 0 5 + -10n = 1 + 0 5 + -10n = 1 Add '-5' to each side of the equation. 5 + -5 + -10n = 1 + -5 Combine like terms: 5 + -5 = 0 0 + -10n = 1 + -5 -10n = 1 + -5 Combine like terms: 1 + -5 = -4 -10n = -4 Divide each side by '-10'. n = 0.4 Simplifying n = 0.4
| 4w^2+28w+40=0 | | 6x=4[x+3] | | 649-x=466 | | (9x-4)(10x+3)= | | -7x=12 | | 82.5-89.4= | | -5(-4)(-4)= | | 5(2x-3)=3x-8 | | x^3-7x^2+4x+12=0 | | 5x-2=3+4x+9 | | 4x=2[y+2] | | 6u+12=0 | | 2.4x=19.2 | | 2+6x=x | | 3t+7=x | | 4.4m-7=3.7[m+2.4] | | 4+5x=6x-7 | | 4.3+1.7x=2.7x | | -15=16x+2 | | -5y^4-3y-7= | | 5x-2=43-4x | | 6xy+18x+24y= | | 10-3n=9n+1 | | 5x^2-6y^2=3 | | 16b^2+4b= | | 3a^2+4a=10x+3x^2-4 | | 4x^2+4y^2=5 | | 18-6x=-60 | | 5x^3-10x^2-25x= | | 24-6x=-6 | | 2x^2-17x=19 | | ln(x-1)=ln(3x) |